Impact of early versus late use of biologic therapy on cumulative surgical rates in patients with IBD - Fairul, Mohd; Nik Muhamad Affendi, Nik Arsyad; Shahrani, Shahreedhan; Xin Hui, Khoo; hilmi, ida normiha (2022)
OBJECTIVE: A treat-to-target therapy in IBD by the early initiation of biologic therapy may impact disease progression and avoidance of surgical-related events. This study aims to identify differences in surgical rates between patients who received early versus late biologic therapy. METHODOLOGY: This was a retrospective study from the UMMC IBD database from January 2009 until January 2022. All biologic experienced patients were included. The time of IBD diagnosis, the time of initiation of biologic therapy from disease onset, the duration of biologic therapy and the time to surgery were collected. Kaplan-Meier curve was used to determine the surgical survival rate with a significant p-value < 0.05. RESULTS: The study included 100 patients bionaïve patients with Crohn’s disease of which n=34, 34% had penetrating and/ or stricturing disease and (n=66, 66%) had non-stricturing non-penetrating disease Patients received Infliximab (n=57, 57%), Ustekunimab (n=16, 16%), Vedolizumab (n=17, 17%) and Adalimumab (n=10, 10%). However, 14% patients had a diagnosis of IBD post-surgery. 69.4% (n=52) patients received early biologic therapy (<2 years from diagnosis) and 39.6% (n=34) patients received late biologic therapy. Cumulative survival surgical rates at 1, 3 and 5 years in the early biologic group were 95%, 90% and 80% (p=0.382) and 85%, 80% and 75% in the late biologic group. CONCLUSION: Although the overall surgical rates were low in patients on biologic therapy, our study failed to show that early biologic therapy had lower cumulative surgical rates probably due to small numbers.